2013
DOI: 10.1096/fasebj.27.1_supplement.1172.9
|View full text |Cite
|
Sign up to set email alerts
|

Differential β‐arrestin2 requirements of constitutive and agonist‐induced internalization of the CB1 cannabinoid receptor

Abstract: CB 1 cannabinoid receptor (CB 1 R) undergoes both constitutive and agonist-induced internalization, but the underlying mechanisms of these processes and the role of βarrestins in the regulation of CB 1 R function are not completely understood. In this study, we followed CB 1 R internalization using confocal microscopy and bioluminescence resonance energy transfer measurements in HeLa and Neuro-2a cells. We found that upon activation CB 1 R binds β-arrestin2 (β-arr2), but not β-arrestin1. Furthermore, both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Distinct patterns can be observed in the resulting bias plots, allowing the SCRAs to be grouped into 6 classes (each represented in Figures 1 and 4C in a different color). Also here, 5F-APINACA (12) and EG-018 (18) (as well as EG-2201 (20) and MDMB-CHMCZCA (21), as shown in Figure S7) stand out as unique SCRAs, clearly displaying distinct shapes in the bias plot as compared to the remaining SCRAs (represented in Figure 4C in dark pink and light blue, respectively). (C8)-CP47497 (1), JWH-250 (6), BB-22 (11), and 5F-CUMYL-PINACA (17) display a pattern similar to that of (S)-5F-MDMB-PINACA (14) (depicted in green in Figure 4C), all showing a subtle preference toward β-arrestin2 signaling.…”
Section: ■ Results and Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Distinct patterns can be observed in the resulting bias plots, allowing the SCRAs to be grouped into 6 classes (each represented in Figures 1 and 4C in a different color). Also here, 5F-APINACA (12) and EG-018 (18) (as well as EG-2201 (20) and MDMB-CHMCZCA (21), as shown in Figure S7) stand out as unique SCRAs, clearly displaying distinct shapes in the bias plot as compared to the remaining SCRAs (represented in Figure 4C in dark pink and light blue, respectively). (C8)-CP47497 (1), JWH-250 (6), BB-22 (11), and 5F-CUMYL-PINACA (17) display a pattern similar to that of (S)-5F-MDMB-PINACA (14) (depicted in green in Figure 4C), all showing a subtle preference toward β-arrestin2 signaling.…”
Section: ■ Results and Discussionmentioning
confidence: 88%
“…Importantly, all these observations are relative to the reference compound CP55940. Apart from the similar profiles for the carbazole-core-containing EG-018 (18), EG-2201 (20), and MDMB-CHMCZCA (21), no obvious structural features could be found that may underlie these distinct patterns. An overview of the bias plots of all SCRAs, individually plotted together with the reference compound CP55940, is given in Figure S7.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Activation of G proteins recruits GRK2/3 via interaction with G protein Gβγ dimer and fosters association between GRK2/3 and the receptor, which is consequently phosphorylated within its intracellular C terminus by the kinase (Homan & Tesmer, 2015; Nogues et al, 2017). Desensitization of CB1R expressed in Xenopus oocytes was shown to be dependent on the presence of both GRK3 and β‐arrestin2 (Daigle, Kearn & Mackie, 2008; Daigle, Kwok, et al, 2008; Gyombolai, Boros, Hunyady & Turu, 2013). Our data are in accord with these findings: the kinase activity of GRK2/3 is essential for efficient β‐arrestin2 recruitment to CB1R.…”
Section: Discussionmentioning
confidence: 99%